Evaluating Speaking Task Design in Netzwerk Neu A1.1: A CEFR- and TBLT-Informed Analysis - Aztiana Aztiana; Lukman Lukman; Prasuri Kuswarini (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study examines and critically analyzes speaking tasks in Netzwerk Neu A1.1 (Chapters 1–6) by evaluating their alignment with principles of German as a Foreign Language (DaF), Task-Based Language Teaching (TBLT), and the Common European Framework of Reference for Languages (CEFR). Using qualitative content analysis, 26 speaking tasks were identified, coded, and categorized based on task type, CEFR communicative activity (spoken interaction or spoken production), interaction mode, and levels of learner output. The findings show that template-based tasks dominate the textbook, accounting for 69.2% of activities, while guided and free production tasks are relatively limited. Spoken interaction is the most prevalent communicative activity (76.9%), reflecting an emphasis on dialogic formats such as short exchanges and role plays. Although this design provides appropriate structural support for beginner learners, the limited use of open-ended and autonomous tasks may restrict the development of fluency, communicative flexibility, and strategic competence. Interviews with seven learners and two instructors reveal that while tasks are generally perceived as accessible and confidence-building, they are also considered repetitive and insufficiently authentic. The study underscores the need to balance structured support with opportunities for spontaneous language use in beginner DaF textbooks.